A deep intronic recurrent CHEK2 variant c.1009-118_1009-87delinsC affects pre-mRNA splicing and contributes to hereditary breast cancer predisposition - Zemankova, Petra; Cerna, Marta; Horackova, Klara; Ernst, Corinna; Soukupova, Jana; Borecka, Marianna; Blümcke, Britta; Cerna, Leona; Cerna, Monika; Curtisova, Vaclava; Dolezalova, Tatana; Duskova, Petra; et al. (Breast (Edinburgh, Scotland), 2024)
Germline CHEK2 pathogenic variants confer an increased risk of female breast cancer (FBC). Here we describe a recurrent germline intronic variant c.1009-118_1009-87delinsC, which showed a splice acceptor shift in RNA analysis, introducing a premature stop codon (p.Tyr337PhefsTer37). The variant was found in 21/10,204 (0.21%) Czech FBC patients compared to 1/3250 (0.03%) controls (p = 0.04) and in 4/3639 (0.11%) FBC patients from an independent German dataset. In addition, we found this variant in 5/2966 (0.17%) Czech (but none of the 443 German) ovarian cancer patients, three of whom developed early-onset tumors. Based on these observations, we classified this variant as likely pathogenic.
Keywords: genetická predispozice k nemoci; Breast cancer; sestřih RNA; Německo; Czech Republic; NGS; Female; Humans; nádory prsu; checkpoint kinasa 2; RNA analysis; Genetic testing; Genetic Predisposition to Disease; RNA Splicing; lidé; zárodečné mutace; Middle Aged; ženské pohlaví; lidé středního věku; prekurzory RNA; Česká republika; Germany; nádory vaječníků; Breast Neoplasms; Germ-Line Mutation; Introns; RNA Precursors; Checkpoint Kinase 2; Ovarian Neoplasms; introny; dospělí; Adult; Deep intronic CHEK2 variant